Sphingolipid Metabolism and Transport in Chlamydia trachomatis and Chlamydia psittaci Infections - Banhart, Sebastian; Schäfer, Elena K.; Gensch, Jean-Marc; Heuer, Dagmar (Frontiers in Cell and Developmental Biology, 2019)
Chlamydia species infect a large range of vertebral hosts and have become of major economic and public health concern over the last decades. They are obligate intracellular bacteria that undergo a unique cycle of development characterized by the presence of two distinct bacterial forms. After infection of the host cell, Chlamydia are found inside a membrane-bound compartment, the inclusion. The surrounding membrane of the inclusion contributes to the host-Chlamydia interface and specific pathogen-derived Inc proteins shape this interface allowing interactions with distinct cellular proteins. In contrast to many other bacteria, Chlamydia species acquire sphingomyelin from the host cell. In recent years a clearer picture of how C. trachomatis acquires this lipid emerged showing that the bacteria interact with vesicular and non-vesicular transport pathways that involve the recruitment of specific RAB proteins and the lipid-transfer protein CERT. These interactions contribute to the development of a new sphingomyelin-producing compartment inside the host cell. Interestingly, recruitment of CERT is conserved among different Chlamydia species including C. psittaci. Here we discuss our current understanding on the molecular mechanisms used by C. trachomatis and C. psittaci to establish these interactions and to create a novel sphingomyelin-producing compartment inside the host cell important for the infection.